Los Recursos Digitales en el Aprendizaje de la Asignatura de Biología animal con los estudiantes de cuarto semestre de la Carrera de Pedagogía de las Ciencias Experimentales: Química y Biología período mayo-septiembre 2021 - León Pinargote, María Auxiliadora (2023)
This research work was carried out given the need to implement digital resources that contribute to learning by relying on new technologies to develop skills and content in the subject of Animal Biology, as well as the use of feasible methodologies that are adaptable to the study modalities currently used in higher education institutions. Also, the need to allow the student to use resources from which they can benefit, for this was proposed as an objective "To analyze the digital resources through a proposal that helps to improve the learning of the subject of Animal Biology with fourth-semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology period May-September 2021", with the development of a user manual that facilitates the use of the proposed resources. The research design was non-experimental, explanatory, field and bibliographic type, descriptive level, using the inductive-deductive method, analysis, and synthesis. The study population consisted of 40 fourth-semester students. For data collection, the survey technique was used with the questionnaire instrument. The results show that 90% of the students consider that using digital resources would support learning Animal Biology. Finally, the proposal facilitated the use and knowledge of the resources, thus promoting not only the use but also the creation of the resources since, according to the results, the use of the resources allows the development of technological skills.